A simulation model for distribution warehouses - Hoyur, Gülizar. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The aim of this study is to aid logistics companies in their strategic and operational decision making processes in a fierce competition environment. With this point of view, an Arena-based simulation model has been developed. This model provides a fast, flexible and effective method to enable the company to understand its warehousing system and the relationship between system elements comprehensively, recognize the effects of the changes on the system in detail, and make immediate and appropriate changes within the system according to the outputs of the model. Strategic decisions include determining the required number of slots and docks, and identifying the necessary amount of labor and equipment during system design of new, large warehouses. The simulation model is a useful tool in the operational decision making process for obtaining valuable knowledge about operational characteristics of the warehouse, planning the shifts, and evaluating needed changes in the amount of fork lifts and labor in case of decrease in the warehouse traffic. Moreover, the model can be utilized to investigate equipment and labor requirements for each hour of a day, if there are scheduled arrivals with definite number of incoming and outgoing trucks. Benefiting from the outputs of the simulation model, the third party logistics company can meet customer expectations of prices, qualities and varieties in warehousing operations more efficiently.
Keywords: Warehouses -- Design and construction.; Computer simulation.; Decision making.